Impact Behavior of Additively Manufactured Stainless Steel Auxetic Structures at Elevated and Reduced Temperatures. Issue 1 (1st October 2020) - Fíla, Tomáš; Koudelka, Petr; Falta, Jan; Šleichrt, Jan; Adorna, Marcel; Zlámal, Petr; Neuhäuserová, Michaela; Mauko, Anja; Valach, Jaroslav; Jiroušek, Ondřej
Abstract : Metamaterials produced using additive manufacturing represent advanced structures with tunable properties and deformation characteristics. However, the manufacturing process, imperfections in geometry, properties of the base material as well as the ambient and operating conditions often result in complex multiparametric dependence of the mechanical response. As the lattice structures are metamaterials that can be tailored for energy absorption applications and impact protection, the investigation of the coupled thermomechanical response and ambient temperature‐dependent properties is particularly important. Herein, the 2D re‐entrant honeycomb auxetic lattice structures additively manufactured from powdered stainless steel are subjected to high strain rate uniaxial compression using split Hopkinson pressure bar (SHPB) at two different strain rates and three different temperatures. An in‐house developed cooling and heating stages are used to control the temperature of the specimen subjected to high strain rate impact loading. Thermal imaging and high‐speed cameras are used to inspect the specimens during the impact. It is shown that the stress–strain response as well as the crushing behavior of the investigated lattice structures are strongly dependent on both initial temperature and strain rate. Abstract : Specimens of an additively manufactured re‐entrant auxetic lattice exhibiting negative in‐plane Poisson's ratio are subjected to high strain rate compression in split Hopkinson pressure bar at two different strain rates and three different temperatures. It is shown that the stress–strain response, as well as the crushing behavior of the lattice, are considerably dependent on both temperature and strain rate.